2017
DOI: 10.1039/c7nj00074j
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physicochemical characterization of sulfonylhydrazone derivatives designed as hypoglycemic agents

Abstract: By solving and refining the structures of two APIs a complete experimental andin silicophysico-chemical characterization was carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…Considering that electrophilicity and steric access to the cyano group are similar between LASSBio-1771 ( 1 ) and LASSBio-1772 ( 2 ), we hypothesized that conformational differences promoted the methyl effect may influence the affinity and intrinsic activity of these prototypes by the oxidative enzymes. This hypothesis agrees with our previous study that revealed conformational differences between LASSBio-1773 ( 3 ) and LASSBio-1774 ( 4 ) …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Considering that electrophilicity and steric access to the cyano group are similar between LASSBio-1771 ( 1 ) and LASSBio-1772 ( 2 ), we hypothesized that conformational differences promoted the methyl effect may influence the affinity and intrinsic activity of these prototypes by the oxidative enzymes. This hypothesis agrees with our previous study that revealed conformational differences between LASSBio-1773 ( 3 ) and LASSBio-1774 ( 4 ) …”
Section: Resultssupporting
confidence: 94%
“…In the M4 metabolite of compound 3 , the dihedral angle H-N–S-C is equal to 176.4°, while in the M5 metabolite of compound 4 , the dihedral angle C-N–S-C is equal to 95.8° (Figure S7). These findings agree with our previous study and support the idea that N -methylation in N -sulfonylhydrazones might influence the recognition of these prototypes upon CYP enzymes. Additionally, our data emphasize how a simple molecular modification could modulate the pharmacokinetics properties, highlighting the importance of metabolite profile investigation in drug discovery …”
Section: Resultssupporting
confidence: 93%
“…X-ray powder diffraction data were used to index the diffraction pattern and to determine the crystal structure of compound 5f (LASSBio-2024). Similar detailed procedures have been reported elsewhere 28–31 . Briefly, compound 5f (LASSBio-2024) crystallized as a monohydrate (C 16 H 14 BN 3 O 4 S⋅H 2 O) in a monoclinic crystal system—space group P 2 1 / c (nr.…”
Section: Resultsmentioning
confidence: 80%
“…The crystal structure of the Nit–OH compound was determined using X-ray powder diffraction data and a simulated annealing approach implemented in DASH software; the detailed procedure is described elsewhere. Nit–OH crystallized in a monoclinic crystal system and space group Pa (nr. 7).…”
Section: Resultsmentioning
confidence: 99%